Remedies in EU competition law substance, process, and policy - Gerard, Damien; Komninos, Assimakis P. (Kluwer Law International B.V., 2020)
Competition authorities intervene with the aim of discontinuing or preventing anti-competitive conduct but also of remedying the consequences thereof and restoring or preserving undistorted competition. In each case, the identification of the appropriate competition law "remedy?" is inherently linked to the identification of harm to competition and the articulation of a theory of harm. To be sure, not all theories of harm can be addressed by means of adequate competition remedies; alternative(regulatory/supervisory) remedies may instead have to be considered. Likewise, whether they are imposed or negotiated, remedies raise different questions, including in terms of judicial review and due process, but also in terms of reach and scope.